Pelatihan Islam Wasathiyah Berkemajuan: Pemberdayaan Perempuan Muda Nasyiatul ‘Aisyiyah DKI Jakarta - Nur Fuad, Ai Fatimah; Basyirah, Rafa (Transformatif : Jurnal Pengabdian Masyarakat, 2023)
Strengthening the understanding of Wasathiyah Islam could be one of the ways to minimize radicalism’s negative impacts to society. In this case, the role of women must also be involved to be at the forefront of mainstreaming wasathiyah Islam or in terms of the Ministry of Religion (Kemenag) called religious moderation. This led us to design a training for Nasyiatul 'Aisyiyah (NA) cadres who can play their roles in the implementation of progressive Islamic wasathiyah within wider society. This training used seminar methods and focus group discussions (FGD) both offline and online. Through intensive discussions during this training, there were participants who apparently still did not have sufficient knowledge and misunderstood Islam wasathiyah. This training, then was very useful in opening the participants' perspective.  NA and female cadres are interested in disseminating and developing the topic of religious moderation or wasathiyah Islam for the wider young and female generation. They believe that strengthening progressive wasathiyah Islam can be a good way to combat radicalism as well as to strengthen the notion of Indonesia’s multiculturalism. The advice from this program emphasizes the importance of formulating effective and sustainable activities by involving various groups so that the benefits are greater within the community.